2008
DOI: 10.1063/1.2831334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zr, Nb, and Cu substitutions on magnetic properties of melt-spun and hot deformed bulk anisotropic nanocomposite SmCo type magnets

Abstract: Structure and magnetic properties of both melt-spun and hot deformed bulk Sm–Co type nanocomposite magnets have been investigated with various metal additions, including Zr, Cu, and Nb. The Zr and Nb additions play important roles in constraining grain growth, resulting in an increase of coercivity Hc. The Cu addition significantly improves the squareness of BH loops as well as the energy product (BH)max. A typical hot deformed bulk anisotropic nanocomposite SmCo type magnet with Mr(hard)∕Mr(easy)∼0.4, Hc∼9kOe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…No noticeable texture was reportedly induced by hot deformation in high-energy ball milled (HEBM) nanocrystalline magnets with R 2 Co 17 as the main phase [6,7]. On the other hand, the texture observed in rapidly solidified Sm-Co--Fe-Zr-(Nb)-Cu-B multiphase magnets after hot deformation [8,9] was attributed to all the Sm-Co phases present in the alloys, including the 2:17 phase. Under certain conditions, the Sm-Co alloys (including Sm 2 Co 17 ) may also adopt the so-called ''1:7'' structure (named after the TbCu 7 [10]), a solid solution of ''dumbbell'' pairs of the Co atoms in the SmCo 5 structure [11][12][13].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…No noticeable texture was reportedly induced by hot deformation in high-energy ball milled (HEBM) nanocrystalline magnets with R 2 Co 17 as the main phase [6,7]. On the other hand, the texture observed in rapidly solidified Sm-Co--Fe-Zr-(Nb)-Cu-B multiphase magnets after hot deformation [8,9] was attributed to all the Sm-Co phases present in the alloys, including the 2:17 phase. Under certain conditions, the Sm-Co alloys (including Sm 2 Co 17 ) may also adopt the so-called ''1:7'' structure (named after the TbCu 7 [10]), a solid solution of ''dumbbell'' pairs of the Co atoms in the SmCo 5 structure [11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…According to [9], the ''1:7'' phase with the composition close to SmCo 5 apparently responds to a hot deformation in a way similar to the SmCo 5 phase, but no deformation studies were reported for the ''1:7'' phase with the composition close to the Sm 2 Co 17 . Finally, the development of texture via hot deformation of the Sm 2 Co 7 structure was characterized in [9] as ''possible''.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Approved for public release; distribution unlimited. Besides fluorine substitution, zirconium, niobium and copper substitutions were studied on samarium cobalt nanocomposite magnets [13]. Increasing zirconium content x from 0.02 to 0.05 led to significant refinement of the grain size in the melt-spun ribbons, from 80-150 to 20-50 nm as estimated by both XRD and SEM analyses.…”
mentioning
confidence: 99%
“…Demagnetization Curves for SmCo Magnet and Sm-Co-Fe Composite Magnets Prepared from Blended and Milled Powder Demagnetization Curves of Bulk Sm-Co/α-(Fe,Co) Magnets as a Function of Milling TimeSubstitution work also done with samarium cobalt based nanocomposites[14] [13]. Fluorine inclusion in alloys of Sm(Co,Fe) z with z >8.5, for nanocomposites of the 2:17 hard phase and Fe-Co soft phase were investigated.…”
mentioning
confidence: 99%